Experimental and computational approach of understanding the gas adsorption in amino functionalized interpenetrated metal organic frameworks (MOFs) - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Journal of Materials Chemistry, 2011)
Two isostructural, three dimensional, interpenetrated, amino (-NH2) functionalized Metal Organic Frameworks [Cd(ANIC)(2)] (Cd-ANIC-1) and [Co(ANIC)(2)] (Co-ANIC-1) with amine-lined pores have been reported. The framework adopts dia topology with interpenetration. Cd-ANIC-1 and Co-ANIC-1 show high CO2 (273 K) and H-2 (77 K) uptake due to the presence of free -NH2 groups and framework interpenetration. The effect of interpenetration and amino functionalization on gas uptake properties of MOFs has been analysed experimentally and computationally, in the isostructural MOFs Cd-ANIC-1 and Co-ANIC-1.